HUBUNGAN INDEKS MASSA TUBUH DENGAN DAYA TAHAN KARDIORESPIRASI PADA WANITA DEWASA - Adela Vania Putri Sion Sinulingga (2023)
Background: The many activities that are carried out by adult women make many adult women pay less attention to their body mass index. Whereas body mass index is one of the important roles in health related to cardiorespiratory endurance problems. Purpose: To determine the relationship between body mass index and cardiorespiratory endurance in adult women. The research location was carried out in Cilalung Village, South Tangerang City in March 2023. To measure cardiorespiratory endurance using the Beep test. Method: This study uses a correlational quantitative research method with a cross sectional approach. The population in this study were all adult women in Cilalung Village, South Tangerang City and 48 samples were taken with an age range of 26-45 years. The benefit of this research is to increase knowledge regarding the relationship between body mass index and cardiorespiratory endurance. Results: The results show that the correlation coefficient between BMI and VO2max is -0.557 with a significance of 0.000. It can be concluded that there is a relationship between body mass index and cardiorespiratory endurance but has a negative correlation coefficient or not in the same direction, where the higher the BMI, the lower the VO2max value.